Evaluation of Community Empowerment Program for Elderly Care: lesson learned from PUSAKA Wahyu Teratai - Syamsumin Kurnia Dewi (Journal of Community Empowerment for Health, 2022)
The current paradigm and health development policy in Indonesia has changed, from development to empowerment. The community empowerment program for elderly care “PUSAKA Wahyu Teratai” is a leading community empowerment programs in the subdistrict of Bambanglipuro, Bantul Regency. This study was conducted to evaluate The PUSAKA Wahyu Teratai program based on input, process, output, and outcome. A Cross-Sectional Study was conducted in December 2019. Data were collected by interviewing caretakers and participants, tracking organizational documents, activity reports, and observing activities implementation. Participant’s quality of life was measured by the Short Form-36 Questionnaire. Evaluation of the input showed: most of the caretakers were male (77.33%), entrepreneurs, senior high school education level (26.67%). Most of the facilities and infrastructure belong to the organization, the principal source of funds from Yayasan Kesejahteraan Sosial Teratai Jakarta, and were sufficient. Evaluation of the process showed: all main activities were well scheduled and carried out routinely and documented. Evaluation of the output showed: the level of participation in each activity is between 67.61% - 100.00%. The outcome evaluation showed: participants with good physical health quality 80.95% and good mental health quality 85.71%. Conclusion: PUSAKA Wahyu Teratai has sufficient capital input, a fair implementation process of activities, and produced better outputs and outcomes.